Return to Play After Treatment of Superior Labral Tears in Professional Baseball Players. (May 2014) - Fedoriw, Wasyl W.; Ramkumar, Prem; McCulloch, Patrick C.; Lintner, David M.
Background: The published return-to-play (RTP) rates for athletes who have undergone surgical repair of superior labrum anterior-posterior (SLAP) tears vary widely and are generally accepted to be lower in the subset of competitive throwers. The efficacy of nonsurgical treatment for this group is unknown. Hypothesis: Nonsurgical treatment of SLAP tears in professional baseball players leads to RTP before consideration of surgical treatment. Incorporating performance statistics and level of competition will result in lower calculated RTP rates than have been previously reported. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review of 119 consecutive patients in a single professional baseball organization with persistent shoulder pain that limited the ability to compete was performed. Sixty-eight patients had magnetic resonance imaging–documented SLAP lesions. All patients had failed 1 attempt at rehabilitation but had continued with supervised physical therapy. Treatment was according to an algorithm focusing on the correction of scapular dyskinesia and posterior capsular contracture with glenohumeral internal rotation deficit (GIRD), followed by pain-free return to throwing. Those who failed 2 cycles of nonsurgical treatment were treated surgically. Success was defined by 2 different standards: (1) RTP, in accordance with previous studies; and (2) a more stringent standard of return to the same level/quality of professional competition (A, AA, AAA, etc) with the incorporation of a return to preinjury individual performance statistics (earned run average, walks plus hits per inning pitched), termed "return to prior performance" (RPP). Results: Sixty-eight athletes were identified with SLAP lesions. Twenty-one pitchers successfully completed the nonsurgical algorithm and attempted a return. Their RTP rate was 40%, and their RPP rate was 22%. The RTP rate for 27 pitchers who underwent 30 procedures was 48%, and the RPP rate was 7%. For 10 position players treated nonsurgically, the RTP rate was 39%, and the RPP rate was 26%. The RTP rate for 13 position players who underwent 15 procedures was 85%, with an RPP rate of 54%. Conclusion: Nonsurgical treatment correcting scapular dyskinesia and GIRD had a reasonable success rate in professional baseball players with painful shoulders and documented SLAP lesions. The rate of return after surgical treatment of SLAP lesions was low for pitchers. The RTP and RPP rates were higher for position players than for pitchers. Nonsurgical treatment should be considered for professional baseball players with documented SLAP lesions, as it can lead to acceptable RTP and RPP rates.